Exact relativistic maxwellian magnetized plasma dielectric tensor evaluation for arbitrary wave numbers - Pavlov, S.S. (Вопросы атомной науки и техники, 2016)
A new exact integral form of the fully relativistic permittivity tensor for plasmas in a magnetic field is given. It is suitable for numerical applications for arbitrary wave numbers since all integrals in it are one-dimensional ones. This form is interesting for applications to study propagation and absorption of electron Bernstein waves in the laboratory thermonuclear plasmas and of arbitrary electron and ion cyclotron waves in the hot astrophysical plasmas.